Differences in Referral Access to Care Between Gastrointestinal Subspecialty Patients: Barriers and Opportunities - Reddy, Kartika (Health Equity, 2018)
Purpose: Referral access to subspecialty care for patients with gastrointestinal (GI) diseases is not well defined, but has significant importance to patients. We hypothesized that patients experience barriers to care in two common gastroenterology subspecialties, Hepatology and Motility, in a university medical center. Methods: Two hundred thirteen clinic patients (mean age 46.5 years; 66.5% female; 85.6% Caucasians) completed a formatted questionnaire on access to care. Hepatology patients were older (49.7 years, p=0.008); motility patients predominantly female (76.8%, p<0.001). Gender distribution was even for hepatology (51.2% female). Both groups were overweight (mean body mass index 28.4). Results: Patients waited a mean 89.5 days to be seen by a subspecialist. There were differences by subspecialty (107.6 days for motility vs. 64.3 days for hepatology, p=0.022). A larger percentage of motility patients were told nothing was wrong with them (16.8%, p<0.01) and could not be helped (42.1%, p=0.000). Conclusions: Access to care for subspecialty gastroenterology patients in a university center appears to be impacted by a number of variables. While there are similarities, differences exist between these two subspecialties. Motility patients were more likely to have been told they have nothing wrong with them, suffer setbacks financially, and suffer mood problems. Their wait time for appointments was also greater than hepatology patients. Further investigations of referral access for gastroenterology patients may yield additional insights into disease-specific barriers to accessing subspecialty care.